2017
DOI: 10.1515/pcssr-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom of the Body in Sport and Exercise Practices

Abstract: IntroductionThe phrase "wisdom of the body" might seem quite absurd at first. This is because wisdom is usually understood as a kind of metaphysical reality -something in our mind, not something that exists in the physical reality or is empirically sensible. Wisdom can be comprehended by reason alone. On the other hand, the body in its activities is not something thoughtful or conscious in and of itself. The body is experienced in and through our senses. Furthermore, the objective empirical science of medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
(4 reference statements)
1
8
0
1
Order By: Relevance
“…However, Plato himself realized the power of the body in shaping the soul and stated that bodily exercises are an important factor in the training of the soul (Plato, 1969). This is similar to what modern psychophysiology has discovered: "Every change in the physiological state is accompanied by an appropriate change in the mental emotional state, conscious or unconscious" (Pisk, 2017). If man is open to receive the messages of the body, it will be seen that the body can contribute to the whole development of man.…”
Section: Wisdom Of the Bodysupporting
confidence: 73%
See 2 more Smart Citations
“…However, Plato himself realized the power of the body in shaping the soul and stated that bodily exercises are an important factor in the training of the soul (Plato, 1969). This is similar to what modern psychophysiology has discovered: "Every change in the physiological state is accompanied by an appropriate change in the mental emotional state, conscious or unconscious" (Pisk, 2017). If man is open to receive the messages of the body, it will be seen that the body can contribute to the whole development of man.…”
Section: Wisdom Of the Bodysupporting
confidence: 73%
“…However, as in ancient times, the happiest and most fulfilled person in modern times is the one who is in harmony with his body. However, it seems that the practice of listening to the body is better preserved in the East than in the West (Pisk, 2017).…”
Section: Wisdom Of the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…69 84 Ovaj se posjed povezuje s naseljem Bekethync koje se dosta često spominje u ispravama pavlinskog samostana na Gariću. 85 Nije sigurno gdje se nalazio, a Pisk pretpostavlja njegov smještaj na područje današnjih mjesta Čaire i Brinjani, dok ga Engel ubicira između Garešnice i Palešnika. 86 Meni se zasad, prema naprijed rečenom, čini da bi ga ipak valjalo tražiti zapadno od Dišnika, na području gdje se danas prostiru predjeli Čičin jarak, Mali Prokop i Pustare, što bi otprilike odgovaralo posjedu Vdeza iz 1256., spomenutom na zapadnoj međi Desnice Berislavovih sinova i Vučetine Zabrudne.…”
Section: Dišnikunclassified
“…Maffulli, Longo, Gougoulias, Loppini, and Denaro (2010) found that elite athletes often risk severe sports injuries to achieve better results. Elite athletes often force the body beyond its capabilities, which causes pain and can even cause injury (Pisk, 2017). According to Sávolt-Szabó (2015), the occurrence of sports injuries and accidents are increasing, as are permanent impairments to health, because of the increasingly higher expectations that increase pressure in competitive sports.…”
mentioning
confidence: 99%